A new species of Parapharyngodon (Oxyuroidea: Pharyngodonidae) infecting Corythomantis greeningi (Anura: Hylidae) from Northeast Brazil - De Sousa-Silva, Charles; Alcantara, Edna Paulino [UNESP]; Ferreira-Silva, Cristiana; Morais, Drausio Honorio; Cascon, Paulo (Taylor & Francis, 2024)
Currently, 56 species of Parapharyngodon are known, with only 12 reported from the Neotropical realm. Parapharyngodon pereiramendoisp. n. is described herein from the host anuran Corythomantis greeningi in the Caatinga biome, a Brazilian semiarid region. In Parapharyngodon pereiramendoisp. n. males present a triangular oral opening with four bilobed lips, each one with a pair of distally located rounded papillae, gubernaculum absent, a short V-shaped support in postanal lips, and three pairs of caudal papillae, while females have three bilobed lips, opening of the postbulbar excretory pore, vulva in equatorial position, and conical tail. Lateral alae are absent in males and females. Here, we describe the 57th species of Parapharyngodon in the world, and the thirteenth from the Neotropical realm, contributing to the taxonomy of the genus Parapharyngodon, as well as increasing the knowledge of helminthfauna in Neotropical hylids. http://www.zoobank.org/urn:lsid:zoobank.org:pub:B064E8A8-170D-4203-9F49-374FC9AF26EE.
Keywords: Amphibians; Caatinga; Nematoda; Neotropical realm; parasitism; taxonomy